Hogyan viselkednek a betétesek? Irodalmi áttekintés; On the behavior of depositors: Literature review - Kiss Hubert János (Hungarian Academy of Sciences, Institute of Economics, 2018)
– The aim of this study is to review what we know about depositors' behavior, using empirical observations and experimental data. I find that both fundamental problems and coordination failures between depositors explain depositors' behavior and therefore the emergence of bank runs. I show that the heterogeneity of depositors matters, because in bank runs different depositors behave in different ways. In the presence (absence) of fundamental problems experience in banking and relationship with the bank increase (decrease) the likelihood of withdrawal. Gender, educational attainment and financial sophistication do not seem to affect systematically if a depositor withdraws her funds from the bank or not. However, social networks (and the information transmitted by them) matter. Deposit insurance reduces the probability of bank runs, but cannot eliminate it. Experimental results are in line with the empirical findings.
Keywords: C91; D8; G4; G21; 330; bank runs; depositors' decisions; empirical data; experiment